Konsep Keluarga Berencana dalam Tinjauan Hukum Islam - Arsul Arsul; Aswar Aswar; Naelah Nur Sofiah (Program Studi Hukum Keluarga Islam (Ahwal Syakhshiyyah), Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2024)
The study was conducted to learn; (1) Review of the concept of family planning. (2) Review of Islamic law regarding the concept of family planning. The study is a library research using the qualitative descriptive. method used in this study is the normative based juridical approach with data colletion techniques wetting trough the stages of identification, classification, veryfing, analysis and deduction. The data obtained the are two primary and secondary data. Primary data collected from Quranic verses and hadith. Secondary data is obtained from some decuments, journals, scripts and related articles. The results of the study indicate that: (1) family planning aims to regulate the number or spacing of children born between husband and wife. The implementation of family planning is known in 2 ways, namely planning parenthood or tanzhim al-nasl which regulates birth spacing, the second is birth control or tahdid al-nasl which limits births. The contraceptive method is indistinguisted by 2 types of traditional contraception namely the method without tools. The second is modern contraception which is carried out with special tools. (2) One of the efforts of the Indonesian goverment in dealing with population is to form the BKKBN. (3) The implementation of family planning in Islam is judgedbased on its objectives namely to manage birth distance (tanzhim al-nasl), not to restrict the number of births (tahdid al-nasl). The method of contraception in Islam is distinguished by the benefits and harms obtained from its use. Islam will prioritize less harmful method such as traditional contraceptive methods. However, seeing its lower effectiveness, with the magnitude of the harm that will occur when the birth arrives, it is permissible to use other methods while maintaining the rules of the sharia. The implication of this study is: (1) for the government to keep trying to mountain and ensure that every citizen is in a better condition in terms of education, health, economy and others. (2) For society it is supposed to be more considerate and considerate of the child she will give birth ti and thus be more beneficial to her, the state and religion. Penelitian ini dilakukan bertujuan untuk mengetahui (1) Tinjauan umum konsep keluarga berencana (2) Tinjauan hukum Islam tentang konsep keluarga berencana. Penelitian ini merupakan penelitian pustaka (Library Research) dengan menggunakan metode deskriptif kualitatif. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif dengan teknik pengumpulan data melalui tahap identifikasi, klasifikasi, verifikasi, analisis dan pembuatan kesimpulan. Data-data yang diperoleh ada 2 yaitu data primer dan data sekunder. Data primer didapatkan dari ayat Al-Quran dan Hadis. Data sekunder didapatkan dari beberapa dokumen, jurnal, skripsi dan artikel yang terkait. Hasil penelitian ini menunjukkan tiga temuan. Pertama, Keluarga Berencana (KB) atau family planning bertujuan untuk mengatur banyaknya jumlah atau jarak kelahiran anak antara pasangan suami dan istri sementara pelaksanaan keluarga berencana dikenal dengan 2 cara yaitu, (1). Planning Parenthood atau tanzhim al-nasl yang mengatur jarak kelahiran, yang (2). Birth Control atau tahdid al-nasl yang membatasi kelahiran. Adapun metode kontrasepsi dibedakan dengan 2 jenis (1). Kontrasepsi trasdisional yaitu metode tanpa alat. (2). Kontrasepsi modern yang dilakukan dengan alat khusus. Kedua., Usaha pemerintah Indonesia dalam menghadapi kependudukan salah satunya adalah dengan membentuk BKKBN. Ketiga, Praktek KB dalam Islam dihukumi berdasarkan tujuannya, yaitu untuk mengatur jarak kelahiran (tanzhim al-nasl) bukan untuk membatasi jumlah kelahiran (tahdid al-nasl). Adapun metode kontrasepsi dalam Islam dibedakan dengan manfaat dan mudarat yang didapatkan dari pemakaiannya. Islam akan lebih mengutamakan yang lebih sedikit mudaratnya seperti metode kontrasepsi tradisional. Namun melihat efektifitasnya yang lebih kecil, dengan besarnya mudarat yang akan terjadi ketika kelahiran itu tiba maka dibolehkan memakai metode lain dengan tetap menjaga aturan syariat.